54.2k views
2 votes
I need the answer to 6x - 9x+ 7= -1

User Bunti
by
4.9k points

2 Answers

5 votes

Answer:

x = 8/3 or 2.67

Explanation:

6x - 9x + 7 = -1

6x - 9x = -3x

-3x + 7 = -1

-7 -7

-3x = -8

/-3 /-3

x = 8/3 or 2.67

User Alexandr Nikitin
by
4.7k points
1 vote

Answer:

x = -8/3

Explanation:

So first let's simplify the expression. Grouping together like terms gives:

-3x + 7 = -1

Subtracting 7 from both sides gives

-3x = -8

Meaning x = -8/3

User Dvenkatsagar
by
4.6k points